D’un « regard-pilote » à l’écart. L’impact de Dubuffet sur les collectes de l’association L’Aracine - Déborah Couette (Les Cahiers de l'École du Louvre)
In 1982 the association L’Aracine was founded ; its aim was to bring together works of art brut in France to make up for the loss of Jean Dubuffet’s Collection de l’Art Brut, transferred from Paris to Lausanne in 1975. The acquisitions on behalf of the L’Aracine collection reflect the influence of Jean Dubuffet, who played the role of adviser and expert for the association. However, the content of the two collections differ. While L’Aracine attempted to reproduce the initial collection identically, this attitude led to a reformulation of the concept of art brut, which finally found itself defined as an artistic category in its own right.